Natural and vaccine-mediated immunity to Salmonella Typhimurium is impaired by the helminth Nippostrongylus brasiliensis. - Saeeda Bobat; Matthew Darby; Dunja Mrdjen; Charlotte Cook; Erin Logan; Jennifer Auret; Elizabeth Jones; Elizabeth Jones; Corinna Schnoeller; Adriana Flores-Langarica; Ewan A Ross; Alykhan Vira; et al. (PLoS Neglected Tropical Diseases)
Background The impact of exposure to multiple pathogens concurrently or consecutively on immune function is unclear. Here, immune responses induced by combinations of the bacterium Salmonella Typhimurium (STm) and the helminth Nippostrongylus brasiliensis (Nb), which causes a murine hookworm infection and an experimental porin protein vaccine against STm, were examined. Methodology/principal findings Mice infected with both STm and Nb induced similar numbers of Th1 and Th2 lymphocytes compared with singly infected mice, as determined by flow cytometry, although lower levels of secreted Th2, but not Th1 cytokines were detected by ELISA after re-stimulation of splenocytes. Furthermore, the density of FoxP3+ T cells in the T zone of co-infected mice was lower compared to mice that only received Nb, but was greater than those that received STm. This reflected the intermediate levels of IL-10 detected from splenocytes. Co-infection compromised clearance of both pathogens, with worms still detectable in mice weeks after they were cleared in the control group. Despite altered control of bacterial and helminth colonization in co-infected mice, robust extrafollicular Th1 and Th2-reflecting immunoglobulin-switching profiles were detected, with IgG2a, IgG1 and IgE plasma cells all detected in parallel. Whilst extrafollicular antibody responses were maintained in the first weeks after co-infection, the GC response was less than that in mice infected with Nb only. Nb infection resulted in some abrogation of the longer-term development of anti-STm IgG responses. This suggested that prior Nb infection may modulate the induction of protective antibody responses to vaccination. To assess this we immunized mice with porins, which confer protection in an antibody-dependent manner, before challenging with STm. Mice that had resolved a Nb infection prior to immunization induced less anti-porin IgG and had compromised protection against infection. Conclusion These findings demonstrate that co-infection can radically alter the development of protective immunity during natural infection and in response to immunization.